The Real-world Efficacy and Safety of Ombitasvir/Paritaprevir/Ritonavir for Hepatitis C Genotype 1 - Miyasaka, Akio (Intern Med, 2018)
OBJECTIVE: There are few reports on the outcomes of 12-week paritaprevir, ombitasvir, and ritonavir (PTV/OBV/r) treatment in real-world clinical settings. We aimed to evaluate the efficacy and safety of 12-week treatment with ritonavir-boosted paritaprevir and ombitasvir in patients with hepatitis C virus (HCV) genotype 1 infection in a real-world setting. METHODS: Fifty-eight patients with chronic hepatitis or compensated hepatic cirrhosis and genotype-1 HCV infection were treated with PTV/OBV/r and followed for 24 weeks after the completion of treatment in 10 centers in northern Tohoku. The efficacy and safety of this 12-week treatment regimen was analyzed. RESULTS: Among the 58 treated patients, 18 (31%) had compensated liver cirrhosis, while 11 (19%) patients had experienced treatment failure with another treatment regimen. NS5A resistance-associated variants (RAVs) were detected at baseline in 3 patients (5.2%), including Y93H in two patients and L31M in two patients. One patient had NS5A RAVs at both positions 93 and 31. The overall sustained virological response (SVR) 24 rate was 96.6%. Three patients with NS5A RAVs also achieved an SVR24. The SVR24 rate was not significantly affected by age, sex, prior treatment, prior history of HCC, or liver stiffness. The mean alanine aminotransferase (ALT) levels decreased significantly during this treatment. Adverse events occurred in 15 patients (26%), 26% of which were grade 1 or 2. No severe adverse events occurred. CONCLUSION: In this real-world study, 12-week PTV/OBV/r treatment was effective and safe for treating patients with HCV-1 infection who had chronic hepatitis or compensated hepatic cirrhosis.